The Corporate Law and the Optimization of Shareholders’ Incomes with Investments into Production Reforming - RODIONOVA, Lyudmila; KANTOR, Olga; RUKHLYADA, Natalia; KARPOVSKAYA, Svetlana (Journal of Advanced Research in Law and Economics, 2016)
In recent years a company’s goal is not profit making but capitalization.  Companies having the capital value larger than their competitors win in the market. This determines the trends in the capital market, namely merger and acquisition, which have been very popular recently in the international market. This paper considers economic statement, formalization and fulfillment of a problem of optimization of management decisions during formation of funds for company development.